Performance Evaluation of Rankiya (Grewia venusta) as a Polymer for Enhanced Oil Recovery-Polymer Flooding - MUHAMMAD, Muhammad Aminu; HASSAN, Usman; ADAMU, Mohammed Bello; AYUBA, Ibrahim; ADAMU, Yahaya Yakubu (ABUAD Journal of Engineering and Applied Sciences, 2024)
Polymer Flooding is an enhanced oil recovery method where high-molecular-weight polymers are added into the injected water, in order to increase the viscosity of injection fluid, improve volumetric sweep efficiency, and finally increase the oil recovery factor. Most research studies focused on the use of partially hydrolysed polyacrylamide (HPAM), xanthan gum, SPG, HEC as flooding fluid. This work focused on investigating the potential of natural polymer - Grewia venusta plant tree in formulating flooding fluid for polymer flooding operation. The polymer was prepared from the mucilage extracted from the inner stem bark of Grewia venusta. Rheological characterization shows that the formulated Grewia venusta mucilage (GVM)-based flooding fluid maintained high viscosity under very high salinity, also exhibits shear thinning behaviour which obeys power law model with fluid behaviour index n = 0.32 and consistency index K= 6.3 at highest GVM concentration of 3000 ppm, similarly revealed that GVM-based flooding fluid was stable when subjected to high salinity of 130,000 ppm and temperature, up to 90 oC an inconsequential decrease in viscosity was experienced. These indicate its potential in enhancing oil recovery process. Core flooding analysis was carried out on an outcrop core sample with porosity and permeability of 26.1% and 218 mD respectively. Core flooding analysis revealed that: with increase in GVM concentration of 500, 750, 1000 and 2000 ppm oil recovered against time were 55.1%, 62.6%, 69.2% and 72.9% respectively, beyond 2000 ppm GVM concentration (optimum concentration), increase in polymer concentration did not bring about an increase in oil recovery, this finally resulted to an incremental recovery of 29% original oil in place (OOIP).